Pengaruh Instagram Ads Terhadap Purchase Intention dada Generasi Milenial (Point Coffee) dengan Brand Awareness dan Brand Image Sebagai Variabel Intervening - Gilbert Billy Rivaldo Matahurila; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
The research aims to assess the effectiveness of Instagram advertising in enhancing brand awareness and image, as well as its influence on purchasing interest. The study targets the millennial demographic in Sidoarjo Regency and its vicinity, aged between 18 to 35 years, selected through a non-probability sampling method. Structural Equation Modeling (SEM) with SmartPLS is employed as the analytical approach. Findings indicate that Instagram advertising positively impacts brand awareness and image. However, brand awareness and image do not influence purchasing interest. Moreover, a direct correlation exists between Instagram advertising and purchase intention, while brand awareness and image do not serve as mediators in this association.